The Effect of Nutritious School Lunches on Education, Health, and Life-Time Income - Petter Lundborg; Dan-Olof Rooth (CESifo Forum, 2022)
In this article we present the long-run gains of adopting a nutritious school meal program for Swedish children. During the 1960s, Sweden rolled out a universal program that provided nutritious school lunches free of charge to all children in Swedish primary schools. Our results show that the school lunch program generated substantial long-term benefits, where pupils exposed to the program during their entire primary school period have 3 percent greater life-time earnings. This effect was greater for pupils from poor households, suggesting that the program reduced socioeconomic inequalities in adulthood. Exposure to the school lunch program also had substantial effects on educational attainment and health.
Keywords: 330